2021
DOI: 10.1186/s40545-021-00347-2
|View full text |Cite
|
Sign up to set email alerts
|

Finding the right balance: implementation of public–private partnership in artemisinin-based combination therapy provision in Manokwari, Indonesia

Abstract: Background Indonesia is the second country with the highest number of malaria cases in Southeast Asia. Private health providers including community pharmacies often become the first point of care for the population seeking malaria treatment; however, public–private partnerships for malaria control are not widely implemented. This paper explores the acceptability of  a public-private partnership program on the  provision of subsidized artemisinin-based combination therapies (ACTs) in community p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Some studies have omitted the construct completely (Bhatti et al, 2021; Gomes et al, 2021) or grouped opportunity cost and burden together (Kuwawenaruwa et al, 2021; Locke et al, 2020) when reporting results, without providing a rationale. We have identified only one study that reported benefits under this theme (Ferdiana et al, 2021). There is already literature (outside the topic of acceptability) that notes that opportunity costs can be positive or negative (Ochalek & Lomas, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have omitted the construct completely (Bhatti et al, 2021; Gomes et al, 2021) or grouped opportunity cost and burden together (Kuwawenaruwa et al, 2021; Locke et al, 2020) when reporting results, without providing a rationale. We have identified only one study that reported benefits under this theme (Ferdiana et al, 2021). There is already literature (outside the topic of acceptability) that notes that opportunity costs can be positive or negative (Ochalek & Lomas, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies used the TFA to develop questionnaires (Aboaja et al, 2021; Sekhon et al, 2022) or online surveys in quantitative approaches to assessment of acceptability (Keyworth et al, 2021; Renko et al, 2020). A small number of studies have reported that the TFA was used to inform an interview guide (Ferdiana et al, 2021; Groarke et al, 2021; Ngowi et al, 2021; Pavlova et al, 2020) although interview guides were not provided with published reports and so it is not possible to describe how the interview questions reflected TFA constructs.…”
Section: Introductionmentioning
confidence: 99%